1991
DOI: 10.1002/ar.1092300104
|View full text |Cite
|
Sign up to set email alerts
|

Subdural compartment in pig: A morphologic study with blood and horseradish peroxidase infused subdurally

Abstract: The dura-arachnoid junction is examined in normal animals and in animals subjected to subdural infusion of blood immediately prior to death, simulating acute subdural hemorrhages. The Norwegian landrace pig is used as the experimental animal. Horseradish peroxidase (HRP) has been added to the injected blood to serve as a macromolecular tracer. The material is studied by light and electron microscopy. Special attention is given to the level of the induced subdural cleavage plane, the total distribution of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
1
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 39 publications
7
72
1
1
Order By: Relevance
“…is formed within the split dural border cell layer." The exprimental data of Orlin et al (1991) also support this fundamental concept. The available evidence from studies on normal animal and human meninges, from investigations on pathological specimens, and from animal experiments, supports the view that the so-called "subdural" hematoma is not subdural in its location but is mainly formed by a splitting open of the DBC layer.…”
Section: A Potential Space?supporting
confidence: 65%
See 3 more Smart Citations
“…is formed within the split dural border cell layer." The exprimental data of Orlin et al (1991) also support this fundamental concept. The available evidence from studies on normal animal and human meninges, from investigations on pathological specimens, and from animal experiments, supports the view that the so-called "subdural" hematoma is not subdural in its location but is mainly formed by a splitting open of the DBC layer.…”
Section: A Potential Space?supporting
confidence: 65%
“…CAPSULE OF THE "SUBDURAL HEMATOMA' If, as has been suggested (Waggener and Beggs, 1967;Nabeshima et al, 1975;Rascol and Izard, 1976;Friede and Schachenmayr, 1978;Friede, 1978, 1979;Yamashima and Friede, 1984;Orlin et al, 1991), the formation of a so-called subdural hematoma is the result of a shearing open of the DBC layer (Figs. 8C, 9A); evidence of the cell type characteristic of this layer should be seen in the capsule surrounding this lesion in human material.…”
Section: A Potential Space?mentioning
confidence: 88%
See 2 more Smart Citations
“…11) Moreover, experiments showed that under normal conditions there is no evidence of the so-called`subdural space.' 9) When animals are subjected to subdural infusion of blood or bleeding takes place into the dural border cell layer, it splits without any particular predestined cleavage plane, although most often the cleavage passes close to the fibrous matter of the dura. The bleeding extends throughout the cerebral and spinal parts of the dural border cell layer and along the spinal nerve roots.…”
Section: Discussionmentioning
confidence: 99%